Transformation of Cultural Identity of the Okokan Tradition in Kediri, Tabanan, Bali - Wulandari, Riza; Gede Lamopia, I Wayan (IPTEK Journal of Proceedings Series, 2020)
Nowadays, the aesthetic value of Okokan performing art has shifted from the sign values replaced by exchange values. This shift is called as a phenomenon of transformation or change that occurs in the Okokan performing art. This study aims to examine the transformation that occurs in the Okokan Traditional Performing Art in Kediri, Tabanan, Bali. Qualitative method is used in solving the problems by taking data through observation, interview, verbal and visual documentation. Based on the findings, the process of the cultural identity transformation of the Okokan performing art includes the transformation of ritual values into profane values. In 1960, the Okokan tradition was carried out only when residents of Kediri had disease outbreak. Year after year, the function of Okokan performing art is shifted to commercialization. Beside of the function, there are changes in the music accompaniment. The existence of popular culture has led the Okokan Tradition being played with modifications of modern musical instruments and dances. The shift also occurs in the use of attributes and dance movements that have followed the current concept.